2022
DOI: 10.3389/fcimb.2022.935322
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol as a potent antifungal agent inhibits Candida albicans virulence factors via the PKC and Cek1 MAPK signaling pathways

Abstract: Magnolol, a lignin compound extracted from Magnolia officinalis Cortex, has been found to have prominent antifungal effects against Candida albicans. However, the specific mechanism still remains unclear. Therefore, this study aimed to further explore the inhibition mechanism of magnolol against Candida albicans virulence factors and the related signaling pathways. By an XTT reduction assay, a hyphal formation assay, confocal laser scanning microscopy, transmission electron microscopy, a calcofluor white stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Magnolol is one of major bioactive isolates from Magnolia officinalis that has many pharmacological activities, including anticancer-, anti-inflammatory-, antifungal-, and antioxidant activities ( Zhang et al., 2019 ; Xie et al., 2022 ). This study showed that magnolol significantly inhibited the growth of various mycoplasma in vitro , including M. synoviae , M. gallisepticum , and M. hyopneumoniae , The MICs of magnolol against various mycoplasma were determined at 15.63 µg/mL, and the inhibitory effect was dose-dependent ( Figures 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnolol is one of major bioactive isolates from Magnolia officinalis that has many pharmacological activities, including anticancer-, anti-inflammatory-, antifungal-, and antioxidant activities ( Zhang et al., 2019 ; Xie et al., 2022 ). This study showed that magnolol significantly inhibited the growth of various mycoplasma in vitro , including M. synoviae , M. gallisepticum , and M. hyopneumoniae , The MICs of magnolol against various mycoplasma were determined at 15.63 µg/mL, and the inhibitory effect was dose-dependent ( Figures 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Magnolol is a traditional Chinese medicine derived from Magnolia officinalis Cortex that displays potent antibacterial-, antifungal-, anti-inflammatory-, and antioxidant activities ( Zhang et al., 2019 ). Magnolol or its derivatives have remarkable antibacterial and antifungal activities against Candida albicans ( Behbehani et al., 2017 ; Xie et al., 2022 ), Streptococcus mutans ( Greenberg et al., 2007 ); Staphylococcus aureus ( Guo et al., 2021 ), Alternaria alternata ( Wang et al., 2020 ), Rhizoctonia solani ( Mo et al., 2021 ), Fusarium ( Oufensou et al., 2019 ), Magnaporthe grisea ( Choi et al., 2009 ), and Penicillium expansum ( Chen et al., 2019 ). Magnolol could damage the integrity of fungal cells and interfere with cell metabolism to inhibit the growth of R. solani and A. alternata ( Wang et al., 2020 ; Mo et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the impaired activation of MAPK-Mkc1 decreased the resistance to ergosterol biosynthesis inhibitors opening the doors to potential upstream agents able to deplete Mkc1 or, in a similar way, Cek1 and Hog1 (Singh et al 2009 ; LaFayette et al 2010 ). In this regard, magnolol negatively affects C. albicans virulence factors by inhibiting PKC and MAPK-Cek1 signaling (Xie et al 2022 ). Finally, another option concerns the inhibition of chaperons of the heat-shock protein family which are involved in the cascades.…”
Section: Therapymentioning
confidence: 99%
“…Magnolol (5,5'-diallyl-2,2'-dihydroxybiphenyl) (The chemical structure of magnolol in Figure 2E) is a polyphenolic binaphthalene compound and a structural isomer of honokiol. Magnolia officinalis Cortex (M. officinalis), as a primary component of traditional Chinese medicine formulae, was widely used for the treatment of infectious diseases associated with pathogenic microorganisms, such as constipation, diarrhea, asthma, phlegm, and malaria (110). Magnolol and honokiol are isolated from the stem bark of a TCM Magnolia officinalis and have a variety of beneficial activities, including anti-inflammatory, antimicrobial, antioxidant, antiangiogenic, anticancer, neuroprotective, cardiovascular protective (111).…”
Section: Magnololmentioning
confidence: 99%